Learning the high bar longswing: II. energetics and the emergence of the coordination pattern - Irwin, G.; Williams, G. K. R.; Kerwin, D. G.; von Lieres und Wilkau, H.; Newell, K. M. (Journal of Sports Sciences, 2021)
This paper is Part II of a study of the effects of practice on young adult novice gymnasts learning the movement coordination pattern of the longswing. The focus was the early stage of learning a critical component of the longswing, namely: through joint motion to inject mechanical energy into the upswing segment effectively to complete the longswing circle. Twenty-five novice male gymnasts received expert instruction while practicing two sessions a week for 3 weeks between a pre- and a post-practice assessment test trial. Seven novices completed a full circle by the end of Test 4. Completion of the longswing was positively related to the angular velocity generated in the gravity driven free fall of the initial segment and the greater rate of energy input in the upward segment. A successful performance in terms of the emergent movement pattern requires coordination of the onset, rate and level of energy input to counterbalance the negative influence of gravity on the second half upwards segment. The development of the complete longswing through the emergence of the collective variable dynamics (Paper 1) and biomechanical energetics of the gymnast (Paper 2) informs coaches, scientists and clinicians regarding task decomposition and learning the longswing.